Pengaturan Pidana Tutupan Bagi Pelaku Tindak Pidana Politik: Tepatkah? - Darryl Evan Brouwer (Amal Insani Foundation, 2023)
Undisclosed punishment is one of the primary penal sanctions in the Indonesian criminal law system. Criminals are imposed on perpetrators who commit criminal acts because they are driven by